SENDOW, I. 2002. Isolation of bluetongue serotypes 1, 6 and 21 from insects in West Java. JITV 7(4): 272-278 - sendow, indrawati (Indonesian Journal of Animal and Veterinary Sciences, 2002)
Bluetongue virus is one of arbovirus diseases which is transmitted by insects, Culicoides spp. Insect collection wasconducted weekly from 1991 to 1993 and forthnightly from 1993 to 1997 in West Java using Pirbright-type miniature light trapin to phosphate buffered saline for identification and viral isolation. A total of 1155 pools of insects were inoculated intoembryonated chicken eggs before passaging in a mosquito cell line and three times blind passages in BHK-21 cells. Fourteenpools of insects produced cytopathic effect in BHK-21 cells. Four of the infected BHK-21 cells reacted in the antigen captureELISA test using a specific monoclonal antibody to bluetongue (BTV) virus. Further identification into serotype in ReferenceLaboratory, indicated that BTV serotype 1 was isolated from C. fulvus, BTV serotype 6 was isolated from C. peregrinus andBTV serotype 21 from pools of C. shortii and C. orientalis.Key words: Bluetongue viruses, isolation, insects